2013
DOI: 10.1016/j.actamat.2013.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of core-loss fine structures to the characterization of ion irradiation damages in the nanolaminated ceramic Ti3AlC2

Abstract: The effect of low energy ion irradiation in the nanolaminated Ti 3 AlC 2 is investigated by means of X-ray diffraction, transmission electron microscopy, electron energy loss and X-ray absorption spectroscopy. The chemical sensitivity and local order probing from core-loss edges provide new insight in the undertanding of structural modifications induced under irradiation. From the analysis of the C K energy loss near edge structure (ELNES) and Al K X-ray absorption near edge structure (XANES) by ab initio calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 68 publications
3
19
0
Order By: Relevance
“…Defect reactions can provide important information on the radiation tolerance of MAX phases. However, they should be verified by experiments and theoretical calculations of migration energy barriers and cascade processes . The present results are consistent with previous DFT studies for Ti 3 AlC 2 and Ti 3 SiC 2 MAX phases …”
Section: Resultssupporting
confidence: 93%
“…Defect reactions can provide important information on the radiation tolerance of MAX phases. However, they should be verified by experiments and theoretical calculations of migration energy barriers and cascade processes . The present results are consistent with previous DFT studies for Ti 3 AlC 2 and Ti 3 SiC 2 MAX phases …”
Section: Resultssupporting
confidence: 93%
“…The space group of this structure (named c-Ti 2 AlC phase) is P63mc with the layer sequence of ABCACB, which is similar to 6H-SiC. In previous study, Bugnet et al [7] investigated the process of phase transition in Ti 3 AlC 2 and found an intermediate c-Ti 3 AlC 2 phase. Based on the assumption that the antisite defects are uniformly distributed, it is deduced that both c-Ti 2 AlC phase and c-Ti 3 AlC 2 phase are transformed in similar ways where the antisite defects and the rearrangement of the C atoms as well as the movement of cation atoms along the basal plane occurred.…”
Section: Microstructure Of the Phase Formed At The Lowest Fluencementioning
confidence: 96%
“…M n + 1 AX n phases (n = 2), especially Ti 3 AlC 2 and Ti 3 SiC 2 , as two typical MAX phases, have been frequently used to investigate the performance under ion irradiation [7][8][9][10][11][12][13][14][15][16]. Similar to Ti 3 AC 2 (A = Al/Si), Ti 2 AlC phase has an isomorphous hexagonal-closepacked structure whose space group is P6 3 /mmc (No.…”
Section: Introductionmentioning
confidence: 99%
“…Some of such phases have also been reported to have good irradiation damage tolerance [7][8][9][10][11][12][13][14][15][16], which leads them to be candidate materials for future fission and fusion reactors with much higher burn-up, requiring the materials to survive up to 200 dpa [17,18]. Ti 3 AlC 2 [10,12,13,19,20] and Ti 3 SiC 2 [7,14,21,22] are two major MAX phases.…”
Section: Introductionmentioning
confidence: 99%